2019
DOI: 10.3390/ma12071071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Arc Pressure on the Digging Process in Variable Polarity Plasma Arc Welding of A5052P Aluminum Alloy

Abstract: The keyhole digging process associated with variable polarity plasma arc (VPPA) welding remains unclear, resulting in poor control of welding stability. The VPPA pressure directly determines the dynamics of the keyhole and weld pool in the digging process. Here, through a high speed camera, high frequency pulsed diode laser light source and X-ray transmission imaging system, we reveal the potential physical phenomenon of a keyhole weld pool. The keyhole depth changes periodically corresponding to the polarity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…On the other hand, in PAW, the arc pressure at 150 A was measured by Xu et al [ 44 ] and Li et al [ 21 ]. It was reported that the maximum values were 3.3 kPa and 3.5 kPa, respectively.…”
Section: Plasma Arc Characteristicsmentioning
confidence: 99%
“…On the other hand, in PAW, the arc pressure at 150 A was measured by Xu et al [ 44 ] and Li et al [ 21 ]. It was reported that the maximum values were 3.3 kPa and 3.5 kPa, respectively.…”
Section: Plasma Arc Characteristicsmentioning
confidence: 99%
“…Thermal joining processes generally involve the butt welding of the busbars (Figure 1d) by laser beam welding [9], electron beam welding [10], and plasma arc welding [11]. Despite the current-carrying capacity being practically unaffected by these joints, their use is constrained by the low absorptivity of the busbar materials, the surface preparation requirements, the large busbar thicknesses, and the difficult applicability in situ.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that by reasonably adjusting and matching the thermal output of the VPPA, the requirements of welding assemblies in multiple fixed positions (e.g., horizontal welding, vertical-up welding, and flat welding) can be realized, which greatly broadens the application scope of this type of welding [ 11 , 12 , 13 , 15 , 16 ]. However, when the position is continuously changed during welding, gravity dynamically influences the keyhole weld pool and makes it difficult to maintain the quasi-stable state of fixed position welding, which becomes unstable during welding, and the metal melt behind the weld pool fluctuates greatly, which can cause intermittent closure or even a lack of closure, thus resulting in uneven weld morphologies and continuous cutting [ 17 ].…”
Section: Introductionmentioning
confidence: 99%